2022
DOI: 10.54371/jiip.v5i11.1083
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kemampuan Literasi Numerasi pada Siswa Kelas 5 SDN Saptorenggo 3 Kabupaten Malang

Abstract: Melalui program Kampus Mengajar ini Kemendikbudristek memberi kesempatan pada mahasiswa dari berbagai jurusan dan program studi untuk mendarmabaktikan kecakapan serta ilmu pengetahuan mereka dalam membantu meningkatkan kemampuan literasi numerasi di jenjang SD dan SMP. Pada penelitian ini, peneliti memberikan lembar kerja (tes mengerjakan soal cerita) untuk melihat kemampuan literasi numerasi siswa. Setelah itu, peneliti juga melakukan wawancara pada guru kelas untuk mengecek keabsahan data dan sebagai salah s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Komponen asessmen yang digunakan dalam proses penilaian itu sendiri adalah bagaimana pembelajaran tersebut memberikan dampak nyata yang terlihat melalui keberhasilan peserta didik (Irmawati & Ilmah, 2022). Hal ini penting dan mempengaruhi terhadap keberhasilan pembelajaran, karena dengan cara ini keberhasilan kompetensi yang dicapai peserta didik dapat diukur dengan lebih baik, dan guru juga dapat menilai kekurangan pembelajaran yang telah selesai berdasarkan penilaian peserta didik yang diberikan.…”
Section: Pendahuluanunclassified
“…Komponen asessmen yang digunakan dalam proses penilaian itu sendiri adalah bagaimana pembelajaran tersebut memberikan dampak nyata yang terlihat melalui keberhasilan peserta didik (Irmawati & Ilmah, 2022). Hal ini penting dan mempengaruhi terhadap keberhasilan pembelajaran, karena dengan cara ini keberhasilan kompetensi yang dicapai peserta didik dapat diukur dengan lebih baik, dan guru juga dapat menilai kekurangan pembelajaran yang telah selesai berdasarkan penilaian peserta didik yang diberikan.…”
Section: Pendahuluanunclassified
“…Research related to literacy and numeracy has been carried out by several previous researchers, including Suryaman (2015), who examined student learning outcomes in reading literacy and the results showed that the average reading ability of Indonesian students was at a low level below the international median; Mahmud and Pratiwi (2019) examined students' numeracy literacy in solving unstructured problems on number material, and the results showed that students were able to solve unstructured problems in the context of everyday life and use analytical interpretations to predict and draw conclusions. However, there are also difficulties experienced by students; Dantes and Handayani (2020) examined school literacy and numeracy through a blended learning model in fifth grade students and the results showed an increase in school literacy and numeracy simultaneously in students with the implementation of the model; Perdana and Suswandari (2021) examined numeracy literacy in thematic learning of upper grade elementary school students and the results showed that numeracy literacy could be carried out by students by providing stimulus to students; Rahmawati (2021) examined numeracy literacy skills in grade 5 and the results showed that most students had low level numeracy literacy skills and the rest were moderate; and lastly, Schult et al (2021) examined reading and mathematics competence of Grade V students in Baden-Württemberg Germany before and after the first wave of the pandemic and the results showed that competency scores in 2020 were slightly lower than in the previous three years. Unlike from existing research, this research focuses on the achievement of literacy and numeracy skills of students in Grades 1 to 5 of elementary schools in coastal areas in Southeast Maluku Regency during Limited Face-to-face Learning.…”
Section: Introductionmentioning
confidence: 99%